(untitled) (Palimpsesto, 2021)
The family microenterprises studies are dominate by the economic and marketing perspectives. However, a little is taken the microenterprises as a mechanism for the labor reintegration of return migrants. Therefore, the objective of this paper is to briefly describe how the entrepreneurship of family micro-businesses contributes to the reintegration of returning migrants into the labor market. The study explores the literature review and analysis of the Sage, Jstor, and Ebsco databases. Among the results, identified that the different types of remittances, migration experience, return conditions, the family’s socioeconomic conditions, and government support through public policies influence entrepreneurship.